Atypical cardiac defects in patients with RASopathies: Updated data on CARNET study. Issue 10 (18th June 2020) - Calcagni, Giulio; Gagliostro, Giulia; Limongelli, Giuseppe; Unolt, Marta; De Luca, Enrica; Digilio, Maria C.; Baban, Anwar; Albanese, Sonia B.; Ferrero, Giovanni B.; Baldassarre, Giuseppina; Agnoletti, Gabriella; Banaudi, Elena; et al.
Abstract: Background: RASopathies are a set of relatively common autosomal dominant clinically and genetically heterogeneous disorders. Cardiac outcomes in terms of mortality and morbidity for common heart defects (such as pulmonary valve stenosis and hypertrophic cardiomyopathy) have been reported. Nevertheless, also Atypical Cardiac Defects (ACDs) are described. The aim of the present study was to report both prevalence and cardiac outcome of ACDs in patients with RASopathies. Methods: A retrospective, multicentric observational study (CArdiac Rasopathy NETwork—CARNET study) was carried out. Clinical, surgical, and genetic data of the patients who were followed until December 2019 were collected. Results: Forty‐five patients out of 440 followed in CARNET centers had ACDs. Noonan Syndrome (NS), NS Multiple Lentigines (NSML) and CardioFacioCutaneous Syndrome (CFCS) were present in 36, 5 and 4 patients, respectively. Median age at last follow‐up was 20.1 years (range 6.9–47 years). Different ACDs were reported, including mitral and aortic valve dysfunction, ascending and descending aortic arch anomalies, coronary arteries dilation, enlargement of left atrial appendage and isolated pulmonary branches diseases. Five patients (11%) underwent cardiac surgery and one of them underwent a second intervention for mitral valve replacement and severe pericardial effusion. No patients died in our cohort until December 2019. Conclusions: Patients with RASopathies present a distinct CHD spectrum. Present data suggest that also ACDs must be carefully investigated for their possible impact on the clinical outcome. A careful longitudinal follow up until the individuals reach an adult age is recommended.